Penerapan Teori Konstruktivisme Jean Piaget Menggunakan Metode Zentangle Dalam Pembelajaran Seni Rupa Siswa SMP - Talensta Mellandika Wardhani; Anik Juwariyah; Warih Handayaningrum (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study is to describe the implementation of Jean Piaget’s constructivist theory using the Zentangle method in visual arts learning for junior high school students. This research employed a descriptive qualitative approach with 30 ninth-grade students of SMP Negeri 1 Nawangan as the research subjects. Data were collected through observation, interviews, and documentation during the visual arts learning process. The results of the study indicate that the application of Jean Piaget’s constructivist theory through the Zentangle method provides a holistic learning approach by engaging students’ cognitive, affective, and psychomotor aspects. Consequently, visual arts learning becomes more meaningful, enhances students’ learning motivation and self-exploration, and improves the quality of students’ learning and artistic practice.